Lessons learned and future business strategies one year after the pandemic - Araujo-Aguirre, Will Erick (2021)
One year after the COVID-19 pandemic, companies had to experience the crisis scenario and overcome it through strategic actions, which left important lessons for the possibility of future crises. The objective of this research was to describe and answer two important questions regarding business practices and lessons during the pandemic, and future policies or strategies in the post-pandemic scenario. The method used was a systematic review of scientific articles, following a bibliographic search strategy in the Scopus database, using some criteria as filters to refine the search. The results show two recurring themes found in the analysis, such as technology and innovation, which are found in most of the strategies and actions implemented by companies; as well as many others measures that are suggested to be put into practice after the end of the pandemic, such as financing and supply policies, among others. Some limitations were the use of a single type of scientific source, few subject areas, and a recognized database for search and analysis.